Studi Pendahuluan Pengembangan Agrotechnopreneurship Potensial di Kabupaten Jember - Wibowo, Yuli; Herlina, Herlina; Soekarno, Siswoyo; Eko Wiyono, Andi; Lailatul Fajriyah, Ajeng Afriska; Windiari, Eva Yulia (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 11 No 1 (2023): Maret, 2023)
This research is a preliminary study to develop potential agrotechnopreneurship in Jember Regency. This study aims to identify agrotechnopreneurship products that can be developed in Jember Regency as a business base for community entrepreneurial activities, as well as an effort to utilize the agricultural potential in Jember Regency. The exploration of agrotechnopreneurship products uses documentation studies, while the determination of potential agrotechnopreneurship products uses the exponential comparison method (MPE). The results showed that the number of agrotechnopreneurship products that were considered feasible to be developed in Jember Regency was 92 products, including products based on livestock sub-sector (4 products), food crops (23 products), plantation (17 products), horticulture (28 products), and fisheries (20 products). Agrotechnopreneurship products are the most potential for community entrepreneurial activities among other products based on aspects of market opportunity, cost, profit potential, and human resource capabilities, namely cow's milk kefir (animal husbandry), mocaf flour (food crops), coconut husk briquettes (plantation), chili sauce (horticulture), and shredded catfish (fishing).